Synbiotic Effect of Probiotic ( Bifidobacterium sp ) and Prebiotics (Chicory and Inulin ) aganist some pathogenic bacteria (Baghdad Science Journal, 2009)
The Antimicrobial activity of Probiotic Bifidobacterium sp and Prebiotics : chicory roots ( Hot water extract ) and Inulin ( 10 % ) against some Pathogenic bacteria (Esherichia coli , Proteus mirabilis , Klebsiella sp , Pseudomonas aeruginosa , Serratia marcescens was studied .The combination of Probiotic and Prebiotics (Synbiotic) (Bifidobacterium sp + chicory ) and (Bifidobacterium sp + Inulin ) also tested for their antimicrobial activity against Pathogenic bacteria .Results showed that Bifidobacterium sp had good antimicrobial activity against all the Pathogenic bacteria tested , followed by chicory and inulin .The synergistic inhibitory effect of Synbiotic (Bifidobacterium sp + chicory ) and ( Bifidobacterium sp + inulin ) on Pathogenic bacteria was higher than the effect of Bifidobacterium sp alone, chicory alone and inulin alone.